Can Dark Matter Halos Change Shape? Examining the Adams Instability in Triaxial Systems - Dowling, Evan (Proceedings of the Wisconsin Space Conference, 2016)
A recently discovered instability causes non-spherical orbits within dark matter halos to exponentially diverge into more spherical orbits. The instability was studied in limited régimes within the Adams et al. (2007) work. This project has replicated and extend the ideas to a static potential system that is accurate to all distances away from the potential’s center as well as found an easy visualization for the arising instability. A better understanding of dark matters’ behavior will help explain dark matters’ halo structure and mass distribution that surround galaxies.